Праве кільце Безу з талією є правим кільцем Ерміта - Гаталевич, А.І. (Український математичний журнал, 2010)
Исследуются некоммутативные кольца, в которых радикал Джекобсона содержит вполне простой идеал. Доказано, что правое кольцо Безу, в котором радикал Джекобсона содержит вполне простой идеал, является правым кольцом Эрмита. Описан новый класс колец Безу, не являющихся кольцами элементарных делителей. We study noncommutative rings in which the Jacobson radical contains a completely prime ideal. It is proved that a right Bézout ring in which the Jacobson radical contains a completely prime ideal is a right Hermite ring. We describe a new class of Bézout rings that are not elementary divisor rings.